Differential expression and properties of starch branching enzyme isoforms in developing wheat endosperm. - Morell, M K (1997)
Three forms of starch branching enzyme (BE) from developing hexaploid wheat (Triticum aestivum) endosperm have been partially purified and characterized. Immunological cross-reactivities indicate that two forms (WBE-IAD, 88 kD, and WBE-IB, 87 kD) are related to the maize BE I class and that WBE-II (88 kD) is related to maize BE II. Comparison of the N-terminal sequences from WBE-IAD and WBE-II with maize and rice BEs confirms these relationships. Evidence is presented from the analysis of nullisomic-tetrasomic wheat lines demonstrating that WBE-IB is located on chromosome 7B and that the WBE-IAD fraction contains polypeptides that are encoded on chromosomes 7A and 7D. The wheat endosperm BE classes are differentially expressed during endosperm development. WBE-II is expressed at a constant level throughout mid and late endosperm development. In contrast, WBE-IAD and WBE-IB are preferentially expressed in late endosperm development. Differences are also observed in the kinetic characteristics of the enzymes. The WBE-I isoforms have a 2- to 5-fold higher affinity for amylose than does WBE-II, and the WBE-I isoforms are activated up to 5-fold by phosphorylated intermediates and inorganic phosphate, whereas WBE-II is activated only 50%. The potential implications of this activation of BE I for starch biosynthesis are discussed.